Centrifugal microextraction tube-cloud point extraction coupled with gas chromatography for simultaneous determination of six phthalate esters in mineral water. Issue 2 (26th November 2014) - Lv, Yun-Kai; Zhang, Wei; Guo, Meng-Meng; Zhao, Fang-Fang; Du, Xiao-Xue
Abstract : In this study, a centrifugal microextraction tube was first fabricated and used for CPE coupled microwave-assisted back-extraction of six phthalates from mineral water. Abstract : A home-made centrifugal microextraction tube (CMET) was developed and applied to cloud point extraction coupled with microwave-assisted back extraction and gas chromatographic separation of six phthalate esters (PAEs) from mineral water. All phthalate esters were entrapped in the micelles of the non-ionic surfactant Triton X-114 and removed from the bulk phase by centrifugation. The obtained surfactant-rich phase was treated with water-immiscible solvents, and the target analytes were back extracted by short-term microwave application and determined by GC-FID directly. The whole process was finished in the CMET. The proposed method demonstrated good performance concerning linearity ( R 2 = 0.9977-0.9998), precision (2.3–5.7%), the limits of detection and quantitation (LOD, 11.5-19.3 μg L −1 ; LOQ, 37.0-63.3 μg L −1 ), spiked recoveries (89.1–96.3%) and enrichment factor (71-85). The proposed method was successfully applied for the determination of trace amount of phthalate esters in mineral water. DBP and BBP were found in actual mineral water samples.